2018
DOI: 10.1371/journal.pone.0197588
|View full text |Cite
|
Sign up to set email alerts
|

Toward quantitative and reproducible clinical use of OCT-Angiography

Abstract: Optical coherence tomography angiography (OCT-A) is an ophthalmic imaging technique which has recently been introduced to clinical use. OCT-A provides visualization of the retinal vascularization in three dimensions, without injection of contrast agents. OCT-A could thus replace the current standard of opthalmic imaging, which is 2D only and requires contrast agents. However, quantitative studies remain to be carried out to assess the full potential of OCT-A. In this context, the present work proposes a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The good or excellent ICCs mean that most of the variation in vessel density quantification is due to individual differences rather than test variability. Previous studies showed the ICCs are good to excellent in repeated measurements on the same day or different days in healthy participants 5,12,14,19,31 and slightly decreased in diseased eyes. 11,13,16,31 Of note, ICCs ≥0.75 were used as the cut-off to represent the excellent ICCs in some of the previous studies, 8,12 while other studies used ICCs ≥0.80 as the excellent ICCs.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The good or excellent ICCs mean that most of the variation in vessel density quantification is due to individual differences rather than test variability. Previous studies showed the ICCs are good to excellent in repeated measurements on the same day or different days in healthy participants 5,12,14,19,31 and slightly decreased in diseased eyes. 11,13,16,31 Of note, ICCs ≥0.75 were used as the cut-off to represent the excellent ICCs in some of the previous studies, 8,12 while other studies used ICCs ≥0.80 as the excellent ICCs.…”
mentioning
confidence: 94%
“…Previous studies showed the ICCs are good to excellent in repeated measurements on the same day or different days in healthy participants 5,12,14,19,31 and slightly decreased in diseased eyes. 11,13,16,31 Of note, ICCs ≥0.75 were used as the cut-off to represent the excellent ICCs in some of the previous studies, 8,12 while other studies used ICCs ≥0.80 as the excellent ICCs. 5 These thresholds are selected based on established guidelines.…”
mentioning
confidence: 94%